Correlation of Subject Characteristics, Work Stress Levels, and Smoking Patterns among Educational Personnel at X University, Indonesia - Makaginsar, Caecielia; Yuniarti, Yuniarti (Global Medical & Health Communication (GMHC), 2024)
Human resources are among the crucial aspects of an organization, including in higher-education organizations. Educational personnel, a key component of the education system, are prone to work stress, which may trigger smoking behavior. Personal characteristics may also influence smoking behavior. This cross-sectional observational analytic study aimed to analyze the relationship between characteristics, work stress level, and smoking behavior of educational personnel of X University, Indonesia. On 30 April–Mei 2021, subjects were recruited through total sampling based on inclusion and exclusion criteria (n=100, all males). A questionnaire that had been tested for validity and reliability was used to collect data on subject characteristics and behaviors, while DASS-42 was used to measure work stress. Age, education level, length of work, and work stress were the independent variables, while smoking was the dependent variable. Data collected were analyzed univariately and bivariately using the chi-square test, with p<0.05 considered significant. Age, education, and length of work were found to be significantly correlated with smoking (p=0.007, 0.016, and 0.009, respectively). However, stress levels did not correlate with smoking (p=0.786). This suggests that age, education, and length of work significantly influence smoking behavior. It's crucial to interpret these findings with caution, especially considering that all subjects are males, who have been proven less prone to stress than females. This caution is necessary to ensure a comprehensive understanding of the factors influencing smoking behavior among educational personnel.